Defective lipid remodeling of GPI anchors in peroxisomal disorders, Zellweger syndrome, and rhizomelic chondrodysplasia punctata - Kanzawa, Noriyuki (The American Society for Biochemistry and Molecular Biology, 2012)
Many cell surface proteins in mammalian cells are anchored to the plasma membrane via glycosylphosphatidylinositol (GPI). The predominant form of mammalian GPI contains 1-alkyl-2-acyl phosphatidylinositol (PI), which is generated by lipid remodeling from diacyl PI. The conversion of diacyl PI to 1-alkyl-2-acyl PI occurs in the ER at the third intermediate in the GPI biosynthetic pathway. This lipid remodeling requires the alkyl-phospholipid biosynthetic pathway in peroxisome. Indeed, cells defective in dihydroxyacetone phosphate acyltransferase (DHAP-AT) or alkyl-DHAP synthase express only the diacyl form of GPI-anchored proteins. A defect in the alkyl-phospholipid biosynthetic pathway causes a peroxisomal disorder, rhizomelic chondrodysplasia punctata (RCDP), and defective biogenesis of peroxisomes causes Zellweger syndrome, both of which are lethal genetic diseases with multiple clinical phenotypes such as psychomotor defects, mental retardation, and skeletal abnormalities. Here, we report that GPI lipid remodeling is defective in cells from patients with Zellweger syndrome having mutations in the peroxisomal biogenesis factors PEX5, PEX16, and PEX19 and in cells from patients with RCDP types 1, 2, and 3 caused by mutations in PEX7, DHAP-AT, and alkyl-DHAP synthase, respectively. Absence of the 1-alkyl-2-acyl form of GPI-anchored proteins might account for some of the complex phenotypes of these two major peroxisomal disorders.